G352 Reviewof Success Transitioning Surviving Adolescents with Congenital Heart Disease to Adult Service- A Single-Centre Observational Study. (7th April 2014) - Yap, NYS; Lewis, C; Yates, R; Kelsall, AW
Abstract : Aim: Advances in paediatric cardiology and surgery over the past 25 years have resulted in increasing number of children with congenital heart disease (CHD) surviving into adulthood. National standards were developed to ensure smooth transitioning of paediatric patients to adult service. To date, there is little data to suggest the best way for successful transition of paediatric patient with CHD. The aim of this study is to review the activity of first follow-up at our Papworth GUCH clinic after transition. Methods: All adolescents aged 15 to 18 years with CHD who attended the transition clinic between September 2009 and September 2013 were identified from the Patient Administration System retrospectively. Their attendance at the first follow-up appointment at Papworth GUCH clinic was recorded. Results: Over the 4 years period, 82 adolescents were seen in the CHD transitional clinic. The ratio of female to male was 1:1.2 and the mean age of transition was 16 years old. A total of 31 patients were excluded from the study, 14 have alternative follow-up arrangement and 17 are yet to be seen. Of the remaining 51 patients who were followed up, 60.8% (31/51) attended their first follow-up appointment, 33.3% did not attend (DNA), 2% cancelled the appointment as the family moved back to America and 4% were unknown. However, for the non-attendance (7), 47.1% (8/17) attended the clinic following a second reminder, 29.4% after a third and 5.9% following the fourth reminder. 17.6% were lost to follow up despite repeat appointments were offered. Conclusion: Providing a new service within a health care system can be difficult with high DNA rate. Although repeat reminder for follow-up appointment is required, this study highlights that the overall attendance at our GUCH service is satisfactory and effective. The advantage of joint transition clinic not only allow us to identify surviving adolescents with CHD but it also ensure that these patients who are at risk of serious complications and premature mortality continue to be followed-up throughout adulthood. Further study to look at their long-term follow up and survival are recommended.